Prediction of Electromagnetic Waves Attenuation due to Rain in the Localities of Lithuania - Tamošiūnaitė, M.; Tamošiūnas, S.; Daukšas, V.; Tamošiūnienė, M.; Žilinskas, M. (Elektronika ir Elektrotechnika, 2010)
The rain attenuation must be taken into account when new Telecommunication systems are projected. Attenuation due to rain depends on the rain rate. The rain rate values exceeded for 0.01% of the time obtained from the data of rainfall amount measured with one – minute intervals of the time must be used in calculation of rain attenuation. One – minute rain rate data are not always readily available from local weather agencies. Only the average annual, daily, hourly or ten – minutes precipitation amounts are available in many cases. The relations between the one – minute rain rate and the value obtained by using the rainfall amount data of longer duration may be used. The one – minute rain rate values in the localities of Lithuania were determined by using the rainfall amount values measured in the Lithuanian weather stations with ten – minutes integration time. They were compared with rain rate –value determined by using model presented in the previous paper and ITU – value. By using the values mentioned above and the known method the one – minute rain rate values were determined. The lowest values of rain rates were obtained in Klaipeda. Using the rain rate value obtained here and the ITU – value, the values of the specific rain attenuation have been determined. The specific rain attenuation values obtained using the local hydro meteorological data measured in Kaunas is by about 2 times higher than ones determined by using the ITU – rain rate – value.